2014
DOI: 10.1007/s00161-014-0381-6
|View full text |Cite
|
Sign up to set email alerts
|

Regular and chaotic oscillations of a Timoshenko beam subjected to mechanical and thermal loadings

Abstract: Dynamics of a Timoshenko beam under an influence of mechanical and thermal loadings is analysed in this paper. Nonlinear geometrical terms and a nonuniform heat distribution are taken into account in the considered model. The mathematical model is represented by a set of partial differential equations (PDEs) which takes into account thermal and mechanical loadings. The problem is simplified to two PDEs and then reduced to ordinary differential equations (ODEs) by means of the Galerkin method taking into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Threedimensional nonlinear motion characteristics of the perfect and imperfect Timoshenko microbeams under mechanical and thermal forces have been examined numerically by Farokhi and Ghayesh [28]. Large amplitude vibrations and regular and chaotic oscillations of a Timoshenko beam under the influence of temperature were analysed by Warminska et al [29,30], and mechanical and thermal loadings have been discussed. Moreover, nonlinear vibration characteristics of cross-ply composite plates in thermal environments were investigated by Settimi et al [31] and Saetta et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…Threedimensional nonlinear motion characteristics of the perfect and imperfect Timoshenko microbeams under mechanical and thermal forces have been examined numerically by Farokhi and Ghayesh [28]. Large amplitude vibrations and regular and chaotic oscillations of a Timoshenko beam under the influence of temperature were analysed by Warminska et al [29,30], and mechanical and thermal loadings have been discussed. Moreover, nonlinear vibration characteristics of cross-ply composite plates in thermal environments were investigated by Settimi et al [31] and Saetta et al [32].…”
Section: Introductionmentioning
confidence: 99%
“…These are determined from the elimination of secular terms at the next level of the approximation. Substituting equations ( 18) into (17)…”
Section: Methodsmentioning
confidence: 99%
“…Primarily, it is on application-based studies rather than emphasizing in accurate measurement of the fatigue. Warminska et al [28] demonstrated that structural response is directed by the level of thermal loading and distribution. A large increase in temperature can shift the vibration centre and it affects the fundamental frequency.…”
Section: Challenge-1: Assessing Fatigue Damage Accurately Under the Vibration-based Loadsmentioning
confidence: 99%